For a More Transparent Governance of Open Source: Seeking the best governance models for FOSS projects. . - Cánovas Izquierdo, Javier Luis; Cabot, Jordi (Communications of the ACM, 2023)
This article reports on how to improve transparent governance of Free and Open Source Software (FOSS). The article presents the current state of FOSS governance using data from Github and builds a roadmap for transparency detailing workflow and decision-making. Topics include the establishment of a governance file located in the root folder of any open source project, the use of a domain-specific language, and the sharing of predefined templates to aid in widespread incorporation of transparency.